KETERLIBATAN MASYARAKAT DALAM PENATAAN RUANG PUBLIK DI PERMUKIMAN PADAT - Hartanti, Nurhikmah Budi; Gandarum, Dedes Nur; Prabowo, Achmad Hadi; Murwonugroho, Wegig; Afandi, Nadya Nurul; Khoirunisa, Amalia (Universitas Trisakti, 2025)
Public spaces are essential elements in any settlement as they serve as avenues for social interaction. However, there is currently a growing concern about the decreasing availability of public spaces, especially in densely populated areas. Kalianyar Subdistrict, located in West Jakarta's Tambora District, is one of the most densely populated areas in DKI (Special Capital Region of Jakarta). It faces issues typical of densely populated areas in general. This area can be considered as not meeting the minimum requirements for infrastructure and environmental facilities, particularly public spaces. There is a need to provide understanding, knowledge, and examples of public space provision through self-organization mechanisms in participatory infrastructure and facility management through Community Empowerment (PKM) activities. The method used involves consultation and guidance with practical demonstrations. The objective of this PKM activity is to enhance the understanding and capabilities of the local community in organizing themselves to participate in creating habitable environments. Through this PKM activity, the identification of expectations, needs, and problems is documented in a written plan for the arrangement of public spaces in the settlement, along with proposed programs from the community regarding the organization of public spaces in RW 07 (a neighborhood unit) of Kalianyar Subdistrict, Tambora District.